PERBANDINGAN HASIL PEMBELAJARAN SPLDV SISWA SECARA DARING DAN LURING PADA MASA TATANAN BARU - Patricia Christe Rompas; Santje M. Salajang; Selfie L. Kumesan (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Learning activities are not as usual due to the Covid-19 pandemic. With several reasons that become shortcomings and limitations for carrying out teaching and learning, the handling of this pandemic makes students have to study online. This study was conducted to determine whether there were differences in student outcomes in online and offline SPLDV materials during the new order. The data for this study used samples from class VIIIA and B of SMP Negeri 4 Tondano. The instrument used is an essay test which is carried out online and offline at different times and places and documentation. From the data analysis of the research results, the average posttest results obtained by the experimental class was 80.46 while for the control class it was 76.26. Based on the results of hypothesis testing using the t-test at the real level =0.05, it was obtained tcount=1,757 and ttable=t((0,05.45))=1,679. Because thitung=1,757 and ttabel=t((0,05.45))=1,679 the statistic value falls in the critical area, so reject H0 and accept H1. It can be concluded that there are differences in student learning outcomes in the SPLDV material which is carried out online and offline.